Protective effects of Bifidobacterium breve on imiquimod-induced psoriasis in mice through secondary bile acid production and FXR-TLR4/NF-κB pathway - Xinqi Chen; Yang Chen; Catherine Stanton; R.Paul Ross; Jianxin Zhao; Bo Yang; Wei Chen (Food Science and Human Wellness)
This study aimed to evaluate the effects of Bifidobacterium breve CCFM683 on psoriasis and to investigate the underlying mechanisms. B. breve CCFM683 significantly ameliorated psoriasis in mice as well as elevated the deoxycholic acid (DCA) and lithocholic acid (LCA) in the colon compared with those of the imiquimod (IMQ)-treated mice. Meanwhile, B. breve CCFM683 increased the relative abundance of DCA-producing Lachnoclostridium and diminished the harmful Desulfovibrio and Prevotellaceae UCG001. Additionally, the farnesoid X receptor (FXR) in the skin was activated and the expression of the Toll-like receptor 4 (TLR4)/ nuclear factor kappa-B (NF-κB) pathway was inhibited, and the downstream interleukin (IL)-17 and tumor necrosis factor (TNF)-α were downregulated whereas IL-10 was up- regulated. Moreover, the subsequent hyperproliferation of keratinocytes and the dysfunction of the epidermal barrier were improved. In conclusion, CCFM683 administration ameliorated IMQ-induced psoriasis via modulating gut microbiota, promoting the DCA production, regulating the FXR -TLR4/NF-κB pathway, diminishing proinflammatory cytokines, and regulating keratinocytes and epidermal barrier. These findings may be conducive to elucidating the mechanism for probiotics to ameliorate psoriasis and to promote its clinical trials in skin disease.